FORMATION AND PROBLEMS IN THE CATERING SYSTEM IN UZBEKISTAN (DURING THE SOVIET PERIOD) - Nasirov, Bunyod; Xusyenova, M (Science technology&Digital finance, 2023)
In the article totalitarian Soviet regime, the process of the formation of public service system, the system of government programs in this area plans and the implementation of these plans in the conflict regions the main problems in the system and information in the case of career in the Soviet republics were analyzed on the basis of the scientific literature, periodicals and archival documents.